Adherence to the Women’s Preventive Services Guidelines in the Affordable Care Act - Tinkle, Mindy B. (J Obstet Gynecol Neonatal Nurs, 2016)
OBJECTIVE: To assess the adherence of women’s health providers in New Mexico to the Women’s Preventive Services Guidelines, now covered as part of the Affordable Care Act, and to examine how providers’ knowledge, attitudes, and external barriers are associated with adherence to these clinical guidelines. DESIGN: Cross-sectional, descriptive survey. SETTING: New Mexico. PARTICIPANTS: Women’s health providers in New Mexico, including nurse practitioners, certified nurse-midwives, and family practice and obstetrician/gynecologist physicians. METHODS: Participants completed a self-administered survey measuring knowledge, attitudes, external barriers, and adherence to each of the eight guidelines. Adherence was defined as following a guideline more than 90% of the time. RESULTS: The response rate was 22% (399/1,798). Among the eight guidelines, participant adherence ranged from 17.2% to 88.4%. Only 39.7% of the participants indicated adherence to a majority of the guidelines (four or more). Overall, provider adherence was directly associated with familiarity with the guidelines (odds ratio [OR], 3.69; 95% confidence interval [CI; 1.96, 6.96]), self-efficacy to implement them (OR, 4.25; 95% CI [2.21, 8.20]), and younger age (OR, 0.97; 95% CI [0.94, 1.00]). CONCLUSION: Adherence to the Women’s Preventive Services Guidelines by providers in New Mexico is variable, and for many recommended practices, is less than optimal. New targeted implementation strategies are needed to address barriers to adherence.